La "Comunidad de lucha" Jaspers-Heidegger. Auge y caída de una amistad - Holzapfel, Cristóbal (Revista de Filosofía, 2007)
The two great German thinkers Karl Jaspers and Martin Heidegger were very close friends. The very fact that they personally met each other on April 8, 1920, in Freiburg im Breisgau, at the celebration of Edmund Husserl’s 61st birthday, may be considered as an historical date in the history of philosophy. Among other things that we find in the “Correspondence” between them, Heidegger says in some letter: “In the silence I always philosophize with you”. Both thinkers proposed to form together a so called “fighting society” (Kampfgemeinschaft), which would seek to introduce a new way of thinking in Germany at that time. This common project is related with the fact that both felt themselves to be marginal thinkers, that did not belong to a philosophy that they dubbed “scholarly”. But this friendship had its peak and fall. What brought the break in 1933 was Heidegger’s adhesion to national-socialism. In fact, they never came together again, although the correspondence was renewed in the post-war period.